Digitised audio questionnaire for assessment of informed consent comprehension in a low-literacy African research population: development and psychometric evaluation. Issue 6 (24th June 2014) - Afolabi, Muhammed O; Bojang, Kalifa; D'Alessandro, Umberto; Ota, Martin O C; Imoukhuede, Egeruan B; Ravinetto, Raffaella; Larson, Heidi J; McGrath, Nuala; Chandramohan, Daniel
Abstract : Objective: To develop and psychometrically evaluate an audio digitised tool for assessment of comprehension of informed consent among low-literacy Gambian research participants. Setting: We conducted this study in the Gambia where a high illiteracy rate and absence of standardised writing formats of local languages pose major challenges for research participants to comprehend consent information. We developed a 34-item questionnaire to assess participants' comprehension of key elements of informed consent. The questionnaire was face validated and content validated by experienced researchers. To bypass the challenge of a lack of standardised writing formats, we audiorecorded the questionnaire in three major Gambian languages: Mandinka, Wolof and Fula. The questionnaire was further developed into an audio computer-assisted interview format. Participants: The digitised questionnaire was administered to 250 participants enrolled in two clinical trials in the urban and rural areas of the Gambia. One week after first administration, the questionnaire was readministered to half of the participants who were randomly selected. Participants were eligible if enrolled in the parent trials and could speak any of the three major Gambian languages. Outcome measure: The primary outcome measure was reliability and validity of the questionnaire. Results: Item reduction by factor analysis showed that 21 of the question items have strong factor loadings. These were retained along with five other items which were fundamental components of informed consent. The 26-item questionnaire has high internal consistency with a Cronbach's α of 0.73–0.79 and an intraclass correlation coefficient of 0.94 (95% CI 0.923 to 0.954). Hypotheses testing also showed that the questionnaire has a positive correlation with a similar questionnaire and discriminates between participants with and without education. Conclusions: We have developed a reliable and valid measure of comprehension of informed consent information for the Gambian context, which might be easily adapted to similar settings. This is a major step towards engendering comprehension of informed consent information among low-literacy participants.